FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERLAMBATAN PASIEN KANKER PAYUDARA DATANG KE RSUP DR. M. DJAMIL PADANG - Narulita, Jaesica Salsabila Dwi; Fortuna, Fory; Semiarty, Rima; Lestari, Yuniar; Oktavenra, Ari; Welan, Rahmani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
West Sumatra ranks third as the province with the highest incidence of breast cancer in Indonesia. Breast cancer is an uncontrolled growth of cells in breast tissue that requires immediate management. Most breast cancer patients seek medical care late, leading to the majority of cases being diagnosed at an advanced stage with a poorer prognosis. Identifying the factors contributing to this delay is crucial. This study aims to examine the relationship between various factors and the delay in patients seeking healthcare services. This research is an analytical observational study with a cross-sectional approach, conducted at RSUP Dr. M. Djamil Padang from August to October 2022, with a total sample of 72 respondents. Data were collected through questionnaires and analyzed using the chi-square test. The results indicate a significant relationship between education level (P = 0.009), knowledge (P = 0.000), fear (P = 0.000), socioeconomic status (P = 0.000), healthcare accessibility (P = 0.000), and the use of alternative medicine (P = 0.000) with delays in seeking healthcare services. However, no significant relationship was found between health insurance (P = 0.499) and social support (P = 0.139) and delays in seeking healthcare services. This study concludes that the factors associated with delays in seeking healthcare services among breast cancer patients include education, knowledge, fear, socioeconomic status, healthcare accessibility, and the use of alternative medicine